HUBUNGAN MODAL SOSIAL DAN KESEJAHTERAAN EKONOMI MASYARAKAT DESA WISATA PONGGOK, KABUPATEN KLATEN - Deca Melani Kristiar Putri; AR Rohman Taufiq Hidayat; Gunawan Prayitno (Badan Perencanaan Pembangunan Daerah Kabupaten Sleman, 2026)
Developing tourism villages is a strategy promoted to accelerate the achievement of SDG Goal 1 (No Poverty). However, empirical evidence across various contexts indicates that tourism village development does not always result in the equitable distribution of economic benefits among local communities. A similar phenomenon is observed in Ponggok Village; while it has achieved economic success through tourism, it currently faces challenges such as declining visitor numbers, issues regarding return on investment and profit-sharing systems, and disparities in economic access among residents. These conditions are thought to stem from differences in trust, norms, and social networks among villagers, making social capital a crucial factor in bridging the gap toward equitable, tourism-based economic prosperity. Therefore, this study aims to examine the relationship between these three dimensions of social capital and the economic well-being of the Ponggok Village community. A quantitative approach was employed, utilizing descriptive statistics, a composite index, Chi-Square tests for supplementary analysis, and Spearman correlation tests for the primary analysis. The results indicate that social capital falls into the